Accessing Legal Information Sources in Turkey - Dedeler Bezirci, Pervin (Information World, 2010)
Currently, like in other fi elds, in the fi eld of law as well, the societal developments, global interactions and the increasing importance of technology in acquiring information resources have led to a rapid augmentation in the number of sources, furthermore, these improvements have resulted in having access to various sources. The great majority of the users of law-relatedinformation are academics, lawyers, judges, students studying law and law consultants. The expectations and demands of these information users are very high. The relevant sources must be immediately reached, the sources in question must be updated, and they have to be accurate and comprehensive. In order to meet such requirements of those users, to know and to apply the means and methods of access to the related information are of essential signifi cance. Thus, this study is an attempt to demonstrate the issue of access to law-related-information in Turkey. Following an initial examination on the general concepts related to the access of information and a brief overview on the key judicial concepts, the study will go on to elucidate the ways and methods of obtaining law-related-information in Turkey.
Keywords: Legal resources; Information resources; Access of information; Turkey